Жіноче письмо, авторка, героїня в українському літературознавстві часів незалежності - Zharkova, Roksolana (Przegląd Wschodnioeuropejski, 2023)
The article is devoted to an analysis of women’s writing in the literary theory and criticism of independent Ukraine. A general overview of the formation of feminist critique and gender approach in Ukrainian literary criticism is made based on the principles of American and French literary schools. Researchers’ concepts concerning the features of women’s writing, themes, stylistics and poetics of texts created by women are analyzed. The achievements of Ukrainian scholars in the study of women’s literature, in particular, the works of modernist and postmodernist women authors, are shown. The leading research themes of the period of Independence are determined, namely: representation and reception of a woman author, features of a text written by a woman, types of heroines in modern Ukrainian women’s prose.